Implementasi Motor Servo MG996r Sebagai Robot Pemegang Batang Nosel Pada Sprayer Elektrik Berbasis Arduino Mega2560 - Rusdiyanto Rusdiyanto; Ibrahim; insani abdi bangsa (Elkom: Jurnal Elektronika dan Komputer, 2021)
The sprayer is one of the equipments that is often used in agriculture, especially in rice plants to control pests and diseases. The use of the nozzle rod on the electric sprayer still uses hands resulting in the spray distance on the rice being not constant. To answer this problem, the researcher will create an innovative robotic hand holding the nozzle rod on an electric sprayer that will direct the nozzle rod constantly. Servo MG996r as a rectifier of the motion of the nozzle stem which will determine the distance and area of ​​spraying on rice. To achieve maximum dispersion in rice with a 4:1 legowo system with a servo rod length of 50 cm and a spacing between rice of 25 cm, the servo must move forward and backward at an angle of 110° - 180° which can be seen on the LCD and the distance of the nozzle rod on the object can be up and down to 38 cm and up 24 cm from the starting position. The results obtained by the robotic hand holding the nose bridge can work optimally.